2018
DOI: 10.1016/j.jvs.2017.07.127
|View full text |Cite
|
Sign up to set email alerts
|

Tibiodistal vein bypass in critical limb ischemia and its role after unsuccessful tibial angioplasty

Abstract: This study showed that tibiodistal vein bypass is a feasible, efficient, and safe technique in patients with critical limb ischemia. It provides acceptable primary and secondary patency rates to prevent major amputation and ensure survival. Previous unsuccessful tibial angioplasty had no significant impact on tibiodistal vein bypass outcome. This technique should be part of the armamentarium of vascular surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…Prior studies 36 , 37 and a recent meta-analysis by Hossain et al 38 have shown that infrainguinal bypass after failed endovascular interventions have worse outcomes compared with primary bypass. Data specific to infrapopliteal bypass after failed tibial intervention are scarce, but a study by Enzmann et al 39 showed that patients undergoing primary tibiodistal vein bypass after failed tibial angioplasty had no impact on outcome compared with a primary tibiodistal vein bypass. In light of the outcomes of the Best Surgical Therapy in Patients With Critical Limb Ischemia (BEST-CLI) study, 12 and until additional data become available, the use of retrograde tibial access should be reserved for a specific cohort of patients with CLTI in which single-segment saphenous vein bypass is not an option.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies 36 , 37 and a recent meta-analysis by Hossain et al 38 have shown that infrainguinal bypass after failed endovascular interventions have worse outcomes compared with primary bypass. Data specific to infrapopliteal bypass after failed tibial intervention are scarce, but a study by Enzmann et al 39 showed that patients undergoing primary tibiodistal vein bypass after failed tibial angioplasty had no impact on outcome compared with a primary tibiodistal vein bypass. In light of the outcomes of the Best Surgical Therapy in Patients With Critical Limb Ischemia (BEST-CLI) study, 12 and until additional data become available, the use of retrograde tibial access should be reserved for a specific cohort of patients with CLTI in which single-segment saphenous vein bypass is not an option.…”
Section: Discussionmentioning
confidence: 99%
“…Auch die Häufigkeit einer Majoramputation war erhöht [35]. Für die Bypassanlage im kruralen oder pedalen Bereich scheinen die Ergebnisse einer sekundären Bypassanlage nach endovaskulärer Therapie nicht signifikant schlechter zu sein, obwohl die primäre Offenheit solcher sekundärer Rekonstruktionen niedriger erschient [36,37,38].…”
Section: Bypass-chirurgie Nach Vorausgegangenem Endovaskulären Therap...unclassified
“…40 Even when tibial angioplasty is unsuccessful, subsequent distal bypass outcomes are not significantly impacted. 41 Conversely, endovascular intervention has been shown to help improve patency of pedal bypasses in patients with CLTI. 42 Bypass graft angioplasty can prolong patency and improve limb salvage in patients with failing pedal grafts.…”
Section: Introductionmentioning
confidence: 99%